Non-formal Education in the Animation of Leisure and Recreation versus the Development of Social Competence - Wioletta Łubkowska; Małgorzata Paczyńska-Jędrycka (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
This article is an empirical study on the possible use of non-formal education in the broadly understood animation of leisure time. The study was conducted using a diagnostic survey method, as well as the techniques of questionnaire and observation, during the last meeting under the project “Non-Formal and Formal Partnership in Adult Education” (Grundtvig Reference Number 2013-RO1- GRU06-29569 2) in Romania, at the turn of February and March 2015. The study included 16 non-formal education trainers from Greece, Latvia, Poland and Romania. The aim of the study was to show the impact of the project on the beneficiaries and the development of their individual social competence, as well as to demonstrate the work techniques of trainers with different social groups. An animator plays an important role in the organization of leisure time of the society, hence their continuous education seems almost necessary. The improvement of individual social competence of the trainers surveyed will certainly contribute to their attempt to pass a various range of games, plays and other activities (including non-formal education) to the participants of the classes.